Stress at work is associated with intima media thickness in older male employees, independent of other sources of stress perception - Mauss, Daniel; Volmer-Thole, Maren; Herr, Raphael; Bosch, Jos A.; Fischer, Joachim E. (Stress, 2021)
Chronic stress at work shows a moderate but robust longitudinal association with cardiovascular disease (CVD). Atherosclerosis is a pathophysiological process of most CVD, for which intima media thickness (IMT) of the carotid artery is used as an early marker. Its relationship with stress at work has remained largely unexplored, and the present study therefore aimed to elucidate the association between stress at work, assessed as effort-reward imbalance (ERI), and IMT. This cross-sectional study comprised of 501 male German employees aged 42 (19-64) years at enrollment into the Mannheim Industrial Cohort Study. Clinical assessments used fasting blood samples and IMT measurement. Self-report questionnaires assessed sources of perceived stress. Analyses adjusted for medical history, life style, and socio-economic status (SES) indicators as well as general perceived stress and worries to determine the specificity of ERI. Linear regression models estimated the association of ERI with IMT, stratifying for age groups and adjusting for potential confounders. ERI ratio increased until the age of 50 years and abated thereafter. In participants younger than 50 years IMT measurements were not associated with ERI ratios. However, despite lower mean ERI ratios in participants older than 50 years, this age group showed a significant relationship with IMT (standardized Beta = .36, p < .01), adjusting for multiple confounders including general perceived stress and worries. These analyses suggest that atherosclerosis in older employees is specifically related to stress at work. Longitudinal studies will help to elucidate the temporal relationship between stress exposure and downstream biological mechanisms.Lay summaryOur study explored the association of job stress and the calcification of the carotid artery in German employees. We found out that this association is stronger in employees older than 50 years. In addition, it is independent of medical risk factors and stress caused by private issues. Our study explored the association of job stress and the calcification of the carotid artery in German employees. We found out that this association is stronger in employees older than 50 years. In addition, it is independent of medical risk factors and stress caused by private issues.
Online publiziert: 2. September 2020
Gesehen am 12.01.2026